A Custom Key-Value Store Hardware on FPGA for IPsec Protocol - Benli, Murat; Ozcan, Erdem; Tureli, Ufuk (IEEE, 2020)
This paper addresses the key-value mechanism used in the IPsec(Internet Protocol Security) security protocol and designed for the unique key selection required in the key distribution infrastructure. Key-value mechanisms are a mechanism used in big data storage centers by many companies such as Intel and Cisco today. Another structure that is an alternative to this mechanism is the CAM (Content Addressable Memory) structure used for routing in LP (Internet Protocol) networks. While describing the key-value mechanism based on the hash algorithm designed in this study, it is compared with its alternatives. The main purpose of the mechanism is to create a fast search mechanism in the memory and not to increase the power and resource consumption while doing this. For this, a hash algorithm has been used, in return, it is necessary to face the conflict problem. XILINX Virtex 7 family FPGA (Field Programmable Gate Array) was used in the study.
Keywords: Engineering